Importing the law? Possible elements of the Mesopotamian legal tradition in New Kingdom Egypt (1549-1064BCE) - Loktionov, Alexandre (BAF-Online: Proceedings of the Berner Altorientalisches Forum, 2025)
Features of New Kingdom (1549-1064BCE[1]) justice not attested earlier• Oracle courts, as attested at Deir el-Medina[2] and elsewhere[3]• Increase in severe corporal punishment: for example, mutilation of nose and ears becomes a standard element in oath formulae[4]• Detailed protasis-apodosis legal decrees, such as the Karnak Decree of Horemheb[5] (1328-1298BCE) or the Nauri Decree of Seti I[6] (1296-1279).  Why might this be connected to Mesopotamia/Semitic law?• “Hyksos” period (1650-1549BCE) immediately prior to New Kingdom• Amarna letters/greater exposure to Akkadian in Egypt during New Kingdom• Legal associations: Akkadian and Egyptian copies of Ramesses II – Hattusili III treaty[7] (1258BCE), where corporal punishment is a prominent topic• Mesopotamian law, and broader scholarship, often associated with protasis-apodosis[8]• Mesopotamian law often associated with severe corporal punishment: for instance, see Code of Hammurabi (1792-1750BCE)[9], Middle Assyrian Laws[10] (c.1400-1100BCE) etc.Why might this NOT be connected to Mesopotamia/Semitic law?• Were earlier periods truly different, or is this down to chance preservation of sources?• Protasis-apodosis has precedents in the Middle Kingdom (2066-1650BCE): for instance, see 2nd Semna stela of Senusret III (1865BCE)[11] or Illahun Medical papyri (c.1800BCE)[12]. [1] All Egyptian dates are calculated according to the chronology set forth in Dodson & Hilton 2004: 287-294, while Mesopotamian dates follow the chronology in van de Mieroop 2007: 302-317.[2] McDowell 1990: 143-186.[3] Kákosy 1975: 600-606; Černy 1962: 35-48.[4] Lorton 1977: 33-38, 50-51; Tyldesley 2000: 81.[5] Kruchten 1981.[6] Kitchen 1975-1990: 53-55 (text 24); Davies 1997: 277-308.[7] Langdon & Gardiner 1920.[8] Bottéro 1992: 125-137, 156-184; Roth 1997.[9] Roth 1997: 71-142; Richardson 2000.[10] Driver & Miles 1935; Roth 1997: 153-194.[11] Sethe 1924: 83-84.[12] Quirke 2002; Collier & Quirke 2004: 53-64.